Comparison of laparoscopic sleeve gastrectomy leak rates in five staple-line reinforcement options: a systematic review - Gagner, Michel (Surg Endosc, 2019)
BACKGROUND: Staple-line leaks following laparoscopic sleeve gastrectomy (LSG) remain a concerning complication. Staple-line buttressing is largely adopted as an acceptable reinforcement but data regarding leaks have been equivocal. This study compared staple-line leaks in five reinforcement options during LSG: no reinforcement (NO-SLR), oversewing (suture), nonabsorbable bovine pericardial strips (BPS), tissue sealant or fibrin glue (Seal), or absorbable polymer membrane (APM). METHODS: This systematic review study of articles published between 2012 and 2016 regarding LSG leak rates aligned with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Variables of interest included leak rates, bleeding, and complications in addition to surgical and population parameters. An independent Fisher’s exact test was used to compare the number of patients with and without leaks for the different reinforcement options. RESULTS: Of the 1633 articles identified, 148 met inclusion criteria and represented 40,653 patients. Differences in age (older in APM; p = 0.001), starting body mass index (lower in Suture; p = 0.008), and distance from pylorus (closer in BPS; p = 0.04) were observed between groups, but mean bougie size was equivalent. The overall leak rate of 1.5% (607 leaks) ranged from 0.7% for APM (significantly lower than all groups; p ≤ 0.007 for next lowest leak rate) to 2.7% (BPS). CONCLUSIONS: This systematic review of staple-line leaks following LSG demonstrated a significantly lower rate using APM staple-line reinforcement as compared to oversewing, use of sealants, BPS reinforcement, or no reinforcement. Variation in surgical technique may also contribute to leak rates. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00464-019-06782-2) contains supplementary material, which is available to authorized users.